A young athlete and the challenges of national identity: The case of Jakov Fak - Bartoluci, S.; Doupona-Topic, M. (Acta Kinesiologica, 2017)
Jakov Fak is a highly successful Croatian/Slovene athlete. When he won a bronze medal for Croatia in 2009, his sport (biathlon) was almost completely unknown to the Croatian public. However, he later appeared in media headlines when he announced his transfer to Slovenia in order to gain better training conditions. In addition to the other challenges in his life (training, hard work, competitions, living space, quality of life, family, etc.), he faced specific challenges regarding his ethnic/national identification. In Croatia (as in many other post-socialist countries), ethnic/national identity is a very important social issue. The case of Jakov Fak is interesting from a sociological perspective because it allows us to observe how individual, sports-related choices brought questions of national (ethnic) identification to the general public, and laid a heavy burden on the shoulders of a young athlete. What should you do when your own country calls you a traitor if you decide to join another country`s team? The issues of training and finding ways to attain success in sports are also closely linked with questions of media attention and national/ethnic discourse in this case as well. This paper deals with the case of Jakov Fak, who made his choices despite having to face challenges unusual for a young athlete.